Anti-inflammatory activity of the Tongmai Yangxin pill in the treatment of coronary heart disease is associated with estrogen receptor and NF-κB signaling pathway. (10th August 2021) - Fan, Yadong; Liu, Jianwei; Miao, Jing; Zhang, Xiaoyu; Yan, Yiqi; Bai, Liding; Chang, Jun; Wang, Ying; Wang, Li; Bian, Yuhong; Zhou, Huifang
Abstract: Ethnopharmacological relevance: The Tongmai Yangxin Pill (TMYX) is a patented traditional Chinese medicine originating from two classic prescriptions, Zhigancao Decoction and Shenmai Yin, which composed of 11 Chinese medicinal herbs: Rehmannia glutinosa (Gaertn.) DC., Spatholobus suberectus Dunn, Ophiopogon japonicus (Thunb.) Ker Gawl., Glycyrrhiza uralensis Fisch., Polygonum multiflorum Thunb., Equus asinus L., Schisandra chinensis (Turcz.) Baill., Codonopsis pilosula (Franch.) Nannf., Chinemys reevesii (Gray), Ziziphus jujuba Mill. and Cinnamomum cassia (L.) J.Presl (Committee of the Pharmacopoeia of PR China, 2015). TMYX has marketed in China for the treatment of chest pain, palpitation, angina, irregular heartbeat and coronary heart disease (CHD) for several decades. Previous studies have confirmed that TMYX can treat CHD by reducing inflammation, but the underlying pharmacological mechanism remains unclear. Aim of the study: This study aimed to declare the underlying pharmacological mechanism of anti-inflammatory activity of TMYX in the treatment of CHD via clinical trial, microarray study, bioinformatics analysis and the vitro assays. Materials and methods: Eight CHD patients' serum biochemical indices including coagulation function, lipid metabolism, endothelial injury, metalloprotease, adhesion molecule, inflammatory mediator and homocysteine were measured to investigate the reduction of CHD risk by TMYX oral administration (40 pills/time, 2 times/day) for eight weeks. The expression profile chips and Ingenuity Pathway Analysis (IPA) were assessed to reveal the global transcriptional response and predict related functions, diseases and canonical pathways. The in vitro anti-inflammatory actions of TMYX were evaluated using oxidized low-density lipoprotein (100 μg/mL) induced murine RAW264.7 macrophage with an ethanol extract from TMYX (EETMYX) (25–100 μg/mL). Results: TMYX treatment showed reduced levels of apolipoprotein B, endothelin 1, nuclear factor κB (NF-κB) and homocysteine in CHD patients. In contrast, the treatment increased the ratio of apolipoprotein A/apolipoprotein B. EETMYX restored cell morphology and suppressed the lipid deposition of the induced foam cells. EETMYX exerted anti-inflammatory effects by raising the mRNA and protein expression of Estrogen receptor 1 (ESR1), blocking the reduction of IκBa level and the phosphorylation of IKKα/β, IκBα and NF-κB p65, accompanied by inhibiting MCP-1, TNF-α and IL-6 production, which were consistent with bioinformatics predictions. Conclusion: TMYX treatment improved the biochemical indices in CHD patients. EETMYX effectively attenuated macrophage foam cell formation and exhibited anti-inflammatory activity is associated with regulating ESR1 and NF-κB signaling pathway activity. Graphical abstract: Image 1